2019
DOI: 10.1002/advs.201902020
|View full text |Cite
|
Sign up to set email alerts
|

Visible Light–Driven Cascade Carbon–Carbon Bond Scission for Organic Transformations and Plastics Recycling

Abstract: Significant efforts are devoted to developing artificial photosynthetic systems to produce fuels and chemicals in order to cope with the exacerbating energy and environmental crises in the world now. Nonetheless, the large-scale reactions that are the focus of the artificial photosynthesis community, such as water splitting, are thus far not economically viable, owing to the existing, cheaper alternatives to the gaseous hydrogen and oxygen products. As a potential substitute for water oxidation, here, a unique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
112
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 87 publications
(113 citation statements)
references
References 76 publications
0
112
0
1
Order By: Relevance
“…As is well-known, photocatalysis is considered as one of the most promising strategy for energy conversion, [14] which includes water splitting, [15] carbon dioxide (CO 2 ) reduction, [16] nitrogen fixation, [17] and even organic transformations. [18] Inspired by these application fields, solar energy can also be used to degrade the plastics under mild conditions. For example, Tadayoshi et al demonstrated that PVC could be photoconverted to CO 2 and hydrogen (H 2 ) over the Pt/TiO 2 photocatalysts at room temperature, [19] while Joydeep et al manifested that the degradation of low-density polyethylene (LDPE) microplastics could be triggered by the ZnO nanorods under visible light irradiation.…”
Section: Solar-driven Conversion Of Plastics Into Carbonaceous Fuelsmentioning
confidence: 99%
“…As is well-known, photocatalysis is considered as one of the most promising strategy for energy conversion, [14] which includes water splitting, [15] carbon dioxide (CO 2 ) reduction, [16] nitrogen fixation, [17] and even organic transformations. [18] Inspired by these application fields, solar energy can also be used to degrade the plastics under mild conditions. For example, Tadayoshi et al demonstrated that PVC could be photoconverted to CO 2 and hydrogen (H 2 ) over the Pt/TiO 2 photocatalysts at room temperature, [19] while Joydeep et al manifested that the degradation of low-density polyethylene (LDPE) microplastics could be triggered by the ZnO nanorods under visible light irradiation.…”
Section: Solar-driven Conversion Of Plastics Into Carbonaceous Fuelsmentioning
confidence: 99%
“…[49] In a typical photochemical reaction, a semiconductor material is employed as a photocatalyst, which generates in-situ photoexcited electron-hole pairs as the active sites to stimulate the redox reactions. [50]…”
Section: Photocatalysismentioning
confidence: 99%
“…[28] To address this, our group developed a novel, visible-lightdriven photocatalytic route using vanadium(V) photocatalysts to selectively cleave the CÀ C bonds of polyethylene, leading to full conversion of polyethylene into formic acid, alkyl formates, and CO 2 . [20] Notably, formic acid is a form of liquid organic hydrogen carrier and a hydrocarbon fuel that reversibly releases CO 2 and can be directly fed into fuel cells, [29] whereas alkyl formates are widely used as refrigerants, solvents, and platform chemicals. [30] Remarkably, this photocatalytic plastics conversion was achieved using a low-power 48 W white light emitting diode (LED), in contrast to the high-power Xenon lamp that is conventionally used for photocatalytic reactions in the literature.…”
Section: Photocatalytic Conversion Of Plastics Into Carbon-neutral Fuelsmentioning
confidence: 99%